Harberger-Laursen-Metzler Effect with Modified Becker-Mulligan Preference by Dynamic Optimization - Deng-Shan Wang; Miao Jin; Zeng-Gang Guo (Discrete Dynamics in Nature and Society)
We investigate the effects of terms-of-trade shocks on the spending and current account where households with the modified Becker-Mulligan endogenous time preference maximize their utility over an infinite planning period. Our results show that, with the modified Becker-Mulligan preference, the effect of the deterioration in terms of trade on the current account depends on people’s characters. However, with the second preference we have considered, the deterioration in terms of trade will result in a current account deficit, which is the same as Obstfeld (1982), where households with Uzawa endogenous time preference are considered; deterioration in terms of trade leads to a decline in the current account. These theoretical results are consistent with the empirical evidence by numerical simulations.